2021
DOI: 10.3389/fgene.2021.746677
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Causal Relationship Between Metabolites and Six Cardiovascular Diseases Based on GWAS Summary Statistics

Abstract: Cardiovascular diseases (CVDs) remain the main cause of morbidity and mortality worldwide. The pathological mechanism and underlying biological processes of these diseases with metabolites remain unclear. In this study, we conducted a two-sample Mendelian randomization (MR) analysis to evaluate the causal effect of metabolites on these diseases by making full use of the latest GWAS summary statistics for 486 metabolites and six major CVDs. Extensive sensitivity analyses were implemented to validate our MR resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…To enhance the rigor of our selection process for instrumental variables (IVs), we employed more stringent criteria compared to a previous study [19]. However, for metabolites with multiple IVs (more than two), several sensitivity analyses were performed to validate the robustness of our findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To enhance the rigor of our selection process for instrumental variables (IVs), we employed more stringent criteria compared to a previous study [19]. However, for metabolites with multiple IVs (more than two), several sensitivity analyses were performed to validate the robustness of our findings.…”
Section: Discussionmentioning
confidence: 99%
“…In the previous Mendelian randomization (MR) analysis from Qiao et al [19], three metabolites, namely N-acetylglycine (OR = 0.95, 95%CI: 0.92-0.97, FDR = 0.023), X-09026 (OR = 0.85, 95%CI: 0.78-0.92, FDR = 0.02), and X-14473 (OR = 0.94, 95%CI: 0.91-0.97, FDR = 0.04), were found to be significantly associated Fig. 3 Bidirectional Mendelian randomization analysis supports causal associations for blood metabolites on hypertension and vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…The scatter plots and funnel plots further substantiate the reliability of these results. Employing the latest GWAS summary data, this study eclipses previous research in terms of scale of exposure data (8299 compared to 7828) and a wider range of metabolites 27 , ensuring a more thorough and rigorous analysis. While the selection criteria were exacting, more lenient conditions were adopted for identifying factors influencing CHD (genome-wide significance level of p<1× 10^-5, r2<0.001 within 10000kb).…”
Section: Reverse Mr Analysis Assessing the Effect Of Chd On Levels Of...mentioning
confidence: 99%
“…Further investigations into the long-term effect are needed to clarify these contradictory results. In addition to obesity-related traits, a study on the causal effect of metabolites on cardiovascular diseases found that acetylglycine is associated with a lower risk of diastolic blood pressure and is considered a potential cause (Qiao et al, 2021). The glycine N-acyltransferase (GLYAT) enzyme, linked with phenylalanine metabolism (Supplementary Figure S4), forms N-acylglycines (Westhuizen et al, 2000) and catalyzes glycine conjugation of acyl-Coa-species, producing intermediate products such as acetylglycine in amino acid and fatty acid metabolism (Badenhorst et al, 2013).…”
Section: Frontiers In Molecular Biosciencesmentioning
confidence: 99%